Microfabricated reciprocating micropump for intracochlear drug delivery with integrated drug/fluid storage and electronically controlled dosing. Issue 5 (18th January 2016) - Tandon, Vishal; Kang, Woo Seok; Robbins, Tremaan A.; Spencer, Abigail J.; Kim, Ernest S.; McKenna, Michael J.; Kujawa, Sharon G.; Fiering, Jason; Pararas, Erin E. L.; Mescher, Mark J.; Sewell, William F.; Borenstein, Jeffrey T.
Abstract : We fabricated a micropump for reciprocating, zero-net-volume intracochlear drug delivery. Abstract : The anatomical and pharmacological inaccessibility of the inner ear is a major challenge in drug-based treatment of auditory disorders. This also makes pharmacokinetic characterization of new drugs with systemic delivery challenging, because efficacy is coupled with how efficiently a drug can reach its target. Direct delivery of drugs to cochlear fluids bypasses pharmacokinetic barriers and helps to minimize systemic toxicity, but anatomical barriers make administration of multiple doses difficult without an automated delivery system. Such a system may be required for hair-cell regeneration treatments, which will likely require timed delivery of several drugs. To address these challenges, we have developed a micropump for controlled, automated inner-ear drug delivery with the ultimate goal of producing a long-term implantable/wearable delivery system. The current pump is designed to be used with a head mount for guinea pigs in preclinical drug characterization experiments. In this system, we have addressed several microfluidic challenges, including maintaining controlled delivery at safe, low flow rates and delivering drug without increasing the volume of fluid in the cochlea. By integrating a drug reservoir and all fluidic components into the microfluidic structure of the pump, we have made the drug delivery system robust compared to previous systems that utilized separate, tubing-connected components. In this study, we characterized the pump's unique infuse–withdraw and on-demand dosing capabilities on the bench and in guinea pig animal models. For the animal experiments, we used DNQX, a glutamate receptor antagonist, as a physiological indicator of drug delivery. DNQX suppresses compound action potentials (CAPs), so we were able to infer the distribution and spreading of the DNQX over time by measuring the changes in CAPs in response to stimuli at several characteristic frequencies.